Markets and Their Virtues. (February 2017) - Miller, Robert C. B.
Abstract: The market economy can be defended using the lens of virtue ethics. Modern virtue ethics was developed originally by the English philosopher Elizabeth Anscombe. Virtue ethics rejects consequentialism and focuses on the virtues. And human nature appears to be collaborative in both language and economic relations exemplified by exchange. By adapting the concept of 'characteristic virtues', developed by Alasdair MacIntyre, it follows that collaboration has its own particular virtues. These virtues can produce prescriptions which mitigate the costs of economic transactions and collaboration. The development of behavioural economics has shown human beings sometimes fall short of the rationality described by neo‐classical microeconomics. But virtuous action tends to correct these deficiencies.